Serum Alanine Aminotransferase (ALT) Activity among Diabetic Patients - Upadhayay, Anshu (International Journal of Applied Sciences and Biotechnology, 2016)
Serum Alanine aminotransferase (ALT) activity is the most common screening test as a part of routine assessment of liver damage. Due to its low activity in extra hepatic tissues an increase in serum ALT is more specific for liver disease. The liver pathology among diabetics is similar to that of alcoholic liver disease, including fatty liver, steatohepatitis, fibrosis, and cirrhosis. Thus, elevated serum ALT activity which is a common sign of liver disease is also observed more frequently in diabetics. This study has been designed with the aim to determine the association of serum ALT activity with diabetes mellitus. The study included 208 subjects attending Nepal police hospital during the time frame 6th October 2009 to 4th January 2010.The ALT activity in serum was determined by kit method, fasting and post prandial sugar was tested by GOD-POD method. Among the total diabetic subjects 43.26% were found to have elevated serum ALT activity (>40IU/L). Diabetic status was found to be significantly associated with ALT activity (p=0.04). In addition to diabetic status body mass index (BMI) was also significantly associated with ALT activity (p=0.02) and higher BMI increases the likelihood of elevated ALT. The association of ALT activity was found to be inverse and significant with age of the patient(r=-0.217, p=0.005). Physical activity was also found to be inversely associated with ALT activity(r=-0.149, p=0.03). Int J Appl Sci Biotechnol, Vol 4(3): 386-390